The craftsman - Sennett, Richard, 1943- (London : Penguin, 2009)
Provocative and enlightening, Richard Sennett's The Craftsman is an exploration of craftsmanship - the desire to do a job well for its own sake - as a template for living. Most of us have to work. But is work just a means to an end? In trying to make a living, have we lost touch with the idea of making things well? Pure competition, Sennett shows, will never produce good work. Instead, the values of the craftsman, whether in a Stradivari violin workshop or a modern laboratory, can enrich our lives and change the way we anchor ourselves in the world around us. The past lives of crafts and craftsmen show us ways of working - using tools, acquiring skills, thinking about materials - which provide rewarding alternative ways for people to utilise their talents. We need to recognize this if motivations are to be understood and lives made as fulfilling as possible.
Originally published: London: Allen Lane, 2008.
Includes bibliographical references and index.
Keywords: Arbeidsmotivatie; Creative ability; Motivatie; Motivation (Psychology).; Work -- Psychological aspects; Work